(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One important parametric family among the life distributions is the exponential fam- ily distributions, which play a central role within the class of all life distributions. Because of their remarkable properties, exponential distributions arise naturally in theoretical settings. It is not surprising, then, that exponential distributions have been overused in applications; but that does not diminish their importance. The im- portance of exponential distribution is partly due to the fact that several of the most commonly used families of life distributions are parametric extensions of this distribu- tion. Such a parametric extension of a particular family of distributions will helps to capture the skewness and peakedness inherent in the data sets, which enables a more realistic modeling of data arising many different real life situations. Also, exponential distribution, with their constant hazard rates, form a baseline for evaluating other parametric families of distributions. One can see much more about this distribution in Balakrishnan and Basu (1995), Johnson et al. (1994), Mann et al. (1974) and Nelson and Wayne (2004). For characterizations of the exponential distribution, see